Developmental Differences Between the Limbic and Neocortical Telencephalic Wall: An Intrasubject Slice-Matched 3 T MRI-Histological Correlative Study in Humans. (11th March 2021) - Bobić-Rasonja, Mihaela; Pogledić, Ivana; Mitter, Christian; Štajduhar, Andrija; Milković-Periša, Marija; Trnski, Sara; Bettelheim, Dieter; Hainfellner, Johannes A; Judaš, Miloš; Prayer, Daniela; Jovanov-Milošević, Nataša
Abstract: The purpose of the study was to investigate the interrelation of the signal intensities and thicknesses of the transient developmental zones in the cingulate and neocortical telencephalic wall, using T2-weighted 3 T-magnetic resonance imaging (MRI) and histological scans from the same brain hemisphere. The study encompassed 24 postmortem fetal brains (15–35 postconceptional weeks, PCW). The measurements were performed using Fiji and NDP.view2. We found that T2w MR signal-intensity curves show a specific regional and developmental stage profile already at 15 PCW. The MRI-histological correlation reveals that the subventricular-intermediate zone (SVZ-IZ) contributes the most to the regional differences in the MRI-profile and zone thicknesses, growing by a factor of 2.01 in the cingulate, and 1.78 in the neocortical wall. The interrelations of zone or wall thicknesses, obtained by both methods, disclose a different rate and extent of shrinkage per region (highest in neocortical subplate and SVZ-IZ) and stage (highest in the early second half of fetal development), distorting the zones' proportion in histological sections. This intrasubject, slice-matched, 3 T correlative MRI-histological study provides important information about regional development of the cortical wall, critical for the design of MRI criteria for prenatal brain monitoring and early detection of cortical or other brain pathologies in human fetuses.